Tele-Active Rehabilitation for adolescents with concussion: a feasibility study. Issue 1 (28th February 2022) - Shore, Josh; Hutchison, Michael G; Nalder, Emily; Reed, Nick; Hunt, Anne
Abstract : Objectives: Active rehabilitation involving subsymptom threshold exercise and education/support promotes recovery among adolescents with concussion, but is typically delivered in-person, which limits accessibility. This study explored the feasibility of a remotely delivered Tele-Active Rehabilitation (Tele-AR) intervention for adolescents with concussion. Methods: A precase–postcase series design was used. Three adolescents (ages 14–17 years) experiencing postconcussion symptoms ≥2 weeks postinjury participated with a parent. The Tele-AR intervention was a 6-week programme supervised by a rehabilitation clinician through weekly videoconferencing appointments and included (1) aerobic exercise, (2) coordination drills and (3) comprehensive education and support. Feasibility indicators included rates of recruitment, retention, adherence, as well as adolescent and parent ratings of technology usability using an adapted Telehealth Usability Questionnaire and satisfaction using the Client Satisfaction Questionnaire-8. Prechanges to postchanges in postconcussion symptoms, illness perceptions, and occupational performance and satisfaction were also assessed. Results: Rates of recruitment (n=3/4) and retention (n=3/3) achieved success criteria. Adherence was high among all participants (77%–100%), and there were no adverse events. Participant ratings of technology usability and satisfaction approached 90%. All participants reported improvements in postconcussion symptoms and illness perception. Clinically significant positive changes were also observed in occupational performance and satisfaction. Conclusions: The Tele-AR intervention appears feasible in a small group of adolescents with concussion, and positive changes were observed in postconcussion symptoms, illness perception and occupational performance. Further study is warranted to evaluate the efficacy of this approach, which may enable access to care that supports recovery in adolescents with concussion.